Mechanical competencies needed for employment in farm machinery sales and service, and farm supplies and equipment businesses - Gentry, Gene A.; Maryland Univ., College Park. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
Objectives were to determine--(1) the mechanical competencies and understandings needed by employees in two off-farm agricultural occupations, and (2) the differences between competencies needed by these employees and successful farmers. David tugend's survey instrument was the basis for an instrument used to interview random samples of 25 businesses selected from each of the two agricultural occupational groups in five Maryland counties (99 farm supplies and equipment businesses and 66 farm sales and service businesses). Employers were asked to evaluate the need for 104 mechanical competencies by sales, skilled, and semiskilled employees. Of the 72 competencies needed, 34 were in farm power and machinery, and 30 were in farm shop work. Recommendations based on this study were--(1) pupils who intend to enter farm machinery sales and service businesses should be given extensive training in farm power and machinery and farm shop work, especially in the areas of welding and metal work, (2) farm shop programs for training pupils should be designed to train for an occupational group rather than a level of employment, and (3) pupils planning to enter farming or farm machinery sales and service businesses should receive mechanical training in the same classes. The 119 skills or competencies identified for this study were ranked and compared with needs identified in a 1963 study of successful farmers in Maryland. (ps)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agricultural Education; Agricultural Machinery Occupations; Educational Needs; Farmers; Mechanical Skills; Off Farm Agricultural Occupations; Sales Occupations; Service Occupations; Vocational Education; Maryland -- Maryland (College Park)